2022
DOI: 10.1101/2022.06.10.22276234
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of Test Positivity on Surveillance with Asymptomatic Carriers

Abstract: Objectives: Recent studies show that Test Positivity Rate (TPR) gain a better correlation than incidence with the number of hospitalized patients in COVID-19 pandemic. Nevertheless, epidemiologist remain sceptical concerning the widespread use of this metric for surveillance, and indicators based on known cases like incidence are still preferred de- spite the large number of asymptomatic carriers which remain unknown. Our aim is to compare TPR and incidence, to determine which of the two has the best characte… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
0
0
Order By: Relevance
“…We know very well that this approach is subject to many limitations and runs the risk of failure. Nonetheless, we have decided to use neither the traditional COVID-19 spread indicators of the classical SIR/SEIR models, nor alternative but simpler regression models [8], because recent studies have shown that more basic and intuitive metrics can establish a better correlation, than traditional indicators, with both the number of hospitalized patients and deaths during a COVID-19 epidemic [9,10]. Even if epidemiologists may remain skeptical about the use of those basic metrics for carrying out a real time surveillance, we are confident that our approach can still be useful to predict deaths over a rather long period of time, essentially because it is not influenced by the large number of asymptomatic carriers which remain still unknown and have often contributed to the failure of traditional epidemiological methods used to modeling the COVID-19 diffusion.…”
mentioning
confidence: 99%
“…We know very well that this approach is subject to many limitations and runs the risk of failure. Nonetheless, we have decided to use neither the traditional COVID-19 spread indicators of the classical SIR/SEIR models, nor alternative but simpler regression models [8], because recent studies have shown that more basic and intuitive metrics can establish a better correlation, than traditional indicators, with both the number of hospitalized patients and deaths during a COVID-19 epidemic [9,10]. Even if epidemiologists may remain skeptical about the use of those basic metrics for carrying out a real time surveillance, we are confident that our approach can still be useful to predict deaths over a rather long period of time, essentially because it is not influenced by the large number of asymptomatic carriers which remain still unknown and have often contributed to the failure of traditional epidemiological methods used to modeling the COVID-19 diffusion.…”
mentioning
confidence: 99%